Pengaruh Keunggulan Produk Pembiayaan Murabahah, Rahn Dan Penerapan Nilai-Nilai Islam Dengan Kualitas Pelayanan Terhadap Kepuasan Nasabah Pada PT BPR Syariah Lantabur Tebuireng Kantor Cabang Gresik - Guffron Abdul Azis; Mukhamad Roni; Taufiq Anshori (JOURNAL OF SHARIA ECONOMICS, 2020)
The objectives of this research were to find the influence of murabahah, rahn financing product superiority and the application of Islamic values ​​with quality of service to customer satisfaction in Islamic banks (PT BPR Syariah Lantabur Tebuireng Cabang Gresik). The approach of this research was quantitative using primary data. The sample in this research were customers of PT BPR Syariah Lantabur Tebuireng Cabang Gresik. With the sampling technique using non-probability sampling, so the authors get a total sample of 75 respondents. Analysis of the data in this research using Smart PLS 2.0 analysis tools. The results showed that Murabahah Financing a significant positive effect on Service Quality. Rahn had a significant positive effect on service quality. Islamic values ​​had a positive and not significant effect on service quality. Service Quality had a significant positive effect on Customer Satisfaction. Murabahah Financing had no significant negative effect on Customer Satisfaction. Rahn had a significant positive significant effect on Customer Satisfaction. Islamic values ​​had an insignificant negative effect on customer satisfaction. From the results of the path test, intervening variables it was service quality proven to be able to mediate the relationship between, Murabahah Financing, Rahn and Islamic Values ​​on customer satisfaction of PT BPR Syariah Lantabur Tebuireng Cabang Gresik. Keywords: Murabahah, Rahn, Islamic Values, Service Quality, Customer Satisfaction.